al-Kafā’atu al-Żātiyyatu Ladā al- Ṭalabati fī Tanfīżi Istirātījiyyāti Ta’līmi ISSO (al-Ta’līmi al-Żātīy wa al-Iyhāiyyati wa al-Muţaşhili al-Mubāsyiri) - Ade Destri Deviana (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2020)
Arabic Learning Concentration centered on writing skills (kitābah) is the teacher's step to perfect the student’s mastery of mahāratu al-lughawiyyah. Its achievement is in accordance with the 2013 curriculum and the needs of students are able to make sentences and practice of qawāid nahwiyah (imlā'), compile simple paragraphs (insha'), and translate (tarjamah). The teacher is also able to direct students to be confident in their ability to do the kitābah assignment which is considered difficult and monotonous by using learning strategies during the government policy for conducting e-learning at home because of the Covid-19 virus. This study uses questionnaires, interviews, and direct participant observation with a qualitative descriptive approach. The sample is 10 grade students in their second semester of MANPK-MAN 4 Banjar Indonesia academic year 2019-2020, aiming to determine students' self-efficacy in the implementation of the kitābah learning strategy, so that students are able to maintain their confidence. The results of the study were students' self-efficacy at a high level with an average value of 3.10 and the kitābah learning strategy used was ISSO (Independent Study, suggestopedia with Online). Independent Study makes students actively study and try to be independent. Suggestopedia as a process of generating student motivation uses sound, film and games. Most students (14%) enjoy online learning because they do not have to go to school, references are available on Google and learning can be done while relaxing. Other students (86%) prefer offline or in class learning because they could meet face to face, interact, understand clearly, be focused and effective. Keywords: Self-Efficacy, Kitābah, Independent Study, Suggestopedia, Online, Covid-19